Answer: 46 years
Step-by-step explanation:
Let the father's age be x and the son's age be y, then 3 years ago:
Father = x - 3
son = y - 3
Then , from the first statement :
x - 3 = 3 ( y - 3 )
x - 3 = 3y - 9
x = 3y - 9 + 3
x = 3y - 6 .......................................... equation 1
In five years time
father = x + 5
son = y + 5
Then , from the second statement
x + 5 = 2 ( y + 5 )
x + 5 = 2y + 10
x = 2y + 10 - 5
x = 2y + 5 ........................ equation 2
Equating equation 1 and 2 , we have
3y -6 = 2y + 5
add 6 to both sides
3y = 2y + 5 + 6
subtract 2y from both sides
3y - 2y = 11
y = 11
substitute y = 11 into equation 1 to find the value of x
x = 3y - 6
x = 3(11) - 6
x = 33 - 6
x = 27
This means that the father is presently 27 years and the son is presently 11 years.
In four years time
father = 27 + 4 = 31
son = 11 + 4 = 15
sum of their ages in four years time will be
31 + 15 = 46 years
<span>The word decreased by means subtract.
So...
Lets look at A.
A: a-b
Sound correct?
No,
Because the sentence said that "a is decreased by the number b."
Lets look at B.
B. b-a
Sound correct?
Yes,
Because a is getting decreased by b.
Your answer is, B.
Hope this helps!(:
</span>
The length of the diagonal of the square is the square root of 32 which equals approximately 5.6569.
The length from the corner to the center of the square is half of the diagonal which is 2.8284. I hope this helps!
X=17+(sqrt(2y)/2),x=17-(sqrt(2y)/2) i believe is the answer